Liquid-liquid equilibrium of the ternary ammonium salt + poly(propylene glycol) + water system - Quintão, Juan C.; Patrício, Pamela R.; Veloso, Anne C. G.; Carvalho, Raquel M. M. de; Silva, Luis H. M. da; Hespanhol, Maria C. (Elsevier Fluid Phase Equilibria, 2017)
Aqueous two-phase systems (ATPS) have been investigated as alternative systems for liquid-liquid extraction. Many ATPS phase diagrams for poly(ethylene glycol) (PEG) have been reported, but little information is available regarding liquid-liquid equilibrium data for poly(propylene glycol) (PPG). In the present work, the phase diagrams for PPG425 + ammonium acetate + H2O, PPG425 + ammonium tartrate + H2O, PPG425 + ammonium citrate + H2O, PPG425 + ammonium formate + H2O, and PEG900 + ammonium citrate + H2O were experimentally determined at 283.2, 298.2, and 313.2 K. The study of statistic treatment was introduced by a computation method NRTL model. This program is a method to estimate the energetic parameters of the studied systems. The binary interaction of the calculated parameters are very important for designing or optimizing industrial process. The results were considered very satisfactory with global root mean square deviations of 1.82%. Factors affecting the phase-forming capability of the polymer + electrolyte + water ATPS, such as anion structure, temperature, polymer hydrophobicity were evaluated. For all the systems, the increase in temperature enlarges the area of the phase diagram, indicating the enthalpic contribution to the formation of the biphasic system. The ability of the different anions to induce ATPS formation with PPG425 followed the order: C4H4O62− (tartrate) > C6H6O72− (citrate) > C2H3O2− (acetate) > CHO2−(formate). The ATPS involving PPG425 showed a larger two-phase area than that observed in the system formed by PEG900, which is more hydrophilic than PPG425.
Keywords: Aqueous two-phase systems; Phase diagram; Poly(propylene glycol); Poly(ethylene glycol); NRTL